Luminescent Polymer Electrolyte Composites Using Silica Coated-Y2O3:Eu as Fillers - Mikrajuddin Abdullah; Kikuo Okuyama (Journal of Engineering and Technological Sciences, 2003)
Luminescent polymer electrolyte composites composed of silica coated Y2O3:Eu in polyethylene glycol (PEG) matrix has been produced by initially synthesizing silica coated Y2O3:Eu and mixing with polyethylene glycol in a lithium salt solution. High luminescence intensity at round 600 nm contributed by electron transitions in Eu3+ (5D0 → 7F0, 5D0 → 7F1, and 5D0 → 7F3 transitions) were observed. The measured electrical conductivity was comparable to that reported for polymer electrolyte composites prepared using passive fillers (non luminescent). This approach is therefore promising for production of high intensity luminescent polymer electrolyte composites for use in development of hybrid battery/display.